Constitutional mismatch repair deficiency syndrome: clinical description in a French cohort. Issue 11 (28th August 2015) - Lavoine, N; Colas, C; Muleris, M; Bodo, S; Duval, A; Entz-Werle, N; Coulet, F; Cabaret, O; Andreiuolo, F; Charpy, C; Sebille, G; Wang, Q; et al.
Abstract : Background: Constitutional mismatch repair deficiency (CMMRD) syndrome is a childhood cancer predisposition syndrome involving biallelic germline mutations of MMR genes, poorly recognised by clinicians so far. Methods: Retrospective review of all 31 patients with CMMRD diagnosed in French genetics laboratories in order to describe the characteristics, treatment and outcome of the malignancies and biological diagnostic data. Results: 67 tumours were diagnosed in 31 patients, 25 (37%) Lynch syndrome-associated malignancies, 22 (33%) brain tumours, 17 (25%) haematological malignancies and 3 (5%) sarcomas. The median age of onset of the first tumour was 6.9 years (1.2–33.5). Overall, 22 patients died, 9 (41%) due to the primary tumour. Median survival after the diagnosis of the primary tumour was 27 months (0.26–213.2). Failure rate seemed to be higher than expected especially for T-cell non-Hodgkin's lymphoma (progression/relapse in 6/12 patients). A familial history of Lynch syndrome was identified in 6/23 families, and consanguinity in 9/23 families. PMS2 mutations (n=18) were more frequent than other mutations ( MSH6 (n=6), MLH1 (n=4) and MSH2 (n=3)). Conclusions: In conclusion, this unselected series of patients confirms the extreme severity of this syndrome with a high mortality rate mostly related to multiple childhood cancers, and highlights the need for its early detection in order to adapt treatment and surveillance.